Chigger mites (Acariformes: Trombiculidae) of Iran - Stekolnikov, Alexandr A.; Saboori, Alireza; Shamsi, Mohsen; Hakimitabar, Masoud (Zootaxa, 2019)
Chigger mites of Iran have been revised based on examination of type materials in the collection of Zoological Museum of Moscow University and reference data. Hitherto, 85 species of trombiculids were recorded in Iran; synonymy, diagnoses, data on depositories of type specimens, lists of hosts and collection localities are given for each species. Original measurements of holotypes or paratypes are provided for 46 species. Four new combinations are proposed: Ornithogastia merops (Vercammen-Grandjean, Rohde and Mesghali, 1970) comb. nov., transferred from Guntherana; O. oenanthe (Vercammen-Grandjean, Rohde and Mesghali, 1970) comb. nov., transferred from Guntherana; Microtrombicula galerida (Vercammen-Grandjean, Rohde and Mesghali, 1970), comb. nov., transferred from Eltonella; and M. meriones (Vercammen-Grandjean, Rohde and Mesghali, 1970), comb. nov., transferred from Eltonella. Comparison of our measurements of holotypes with those given in the original species descriptions published by Kudryashova was carried out using statistical methods to establish probable systematic bias between metric data obtained by different researchers. A key to species of Iranian trombiculid larvae is compiled. With the use of public geoinformation online resources, actual names and coordinates were established for all 48 sites of Iran where chigger mites were collected.